STАTUTА PSSI DALAM HIERARKI PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Muhammad Ajid Husain (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
AbstractThe legal standing of PSSI statute is still a pros and cons among legal experts and football activists in Indonesia. This is because there are two views, namely the first view that the pssi statute is Lex Sportiva that has national legal immunity, while the second view considers the pssi statute can not override the national law in force in Indonesia. This research uses normative legal research methods. Based on the research conducted, the Statute of PSSI as Lex Sportiva is only the rule of play and not as the rule of law as stated in Article 7 paragraph (1) of the Law on the Establishment of Legislation containing the types of laws and regulations in Indonesia. Future arrangements regarding the position of the PSSI statutes can be made by revising the laws of the national sports system or by issuing new laws and regulations governing the division of authority between the Government and PSSI as well as applying criminal sanctions related to persecution and scoring arrangements in football matches. Keyword: PSSI Statute; Lex Sportiva; Sports Law;